Article Review: Analisis Zat Berbahaya PadaProdukKosmetik Perona Bibir dengan Berbagai Metode Analisis - Nadia Magfira Nurmalasanti; Windah Anugrah Subaidah (Universitas Muhammadiyah Klaten, 2026)
In lip color cosmetic products, dangerous additional ingredients that can be found, include heavy metal contamination such as lead (Pb), mercury (Hg), cadmium (Cd), and nickel (Ni) which can come from raw materials or enter from the external environment during the production process. Apart from that, there are also many found the red dye K10 (Rhodamine B), which is a strong synthetic dye. This article aims to provide information regarding the use of analytical methods that can be used to identify dangerous substances that are usually contained in lip color cosmetic products. The writing method used in this article review is literature study conducted through the search of journals and scientific articles via the internet. From this search, 18 literature sources were obtained that analyzed lip color products using various analytical methods. The analytical methods that can be employed include, Atomic Absorption Spectrophotometry (AAS), Thin Layer Chromatography (TLC), UV-VIS Spectrophotometry, High-Performance Liquid Chromatography (HPLC), and Paper Chromatography. Among these methods, AAS is frequently used to analyze metal substances, while UV-VIS Spectrophotometry is most commonly used for detecting dyes.